EISCAT Svalbard radar observations of ionospheric signatures of magnetopause reconnection during a changing IMF Bz polarity - S. E. Pryse; A. M. Smith; L. Kersley; I. W. McCrea (Annales Geophysicae, 2002)
Observations by the EISCAT Svalbard radar are presented that show the response of the spatial structure of the ionosphere in the dayside cusp region to a rotational trend in the IMF clock angle. Over a period of one hour, the clock angle increased from about 45° to some 150°, moving the likely location of the magnetopause reconnection site from the high-latitude lobe to near the equatorial plane. Increased topside electron temperatures measured by the ESR identified footprints of the reconnection process. Temporal changes in the spatial distribution of the temperature reflected the change from lobe to equatorial reconnection. Discrete spatial enhancements in ion temperature were found resulting from ion-neutral frictional heating in the fast flows where it was likely that field lines were being convected from the reconnection locations. The corresponding electron density structuring is interpreted in terms of the particle precipitation, field-aligned currents and convection flows driven by the IMF. Key words. Ionosphere (ionosphere – magnetosphere interactions; plasma temperature and density; polar ionosphere)